Rice Seedlings Growth at Multiple Shelves and Light Substitution in Greenhouse - Widyawati, Nugraheni; Kurnia, Theresa Dwi; Simanjuntak, Bistok Hasiholan; Setiawan, Andree Wijaya (Agrotechnology Research Journal, 2024)
Rice is Indonesia’s first staple food crop, planted throughout the year in irrigated rice fields. Finding an efficient method of producing rice seedlings outside the paddy fields is necessary. This research aims to determine the optimal shelf levels in open fields to support seedling rice growth and chlorophyll content and identify suitable lighting alternatives to light-emitting diode (LED) growth lights for supporting indoor seedling rice growth. This study used thirteen treatment variations, each repeated five times in a Randomized Block Design. The observational data were analyzed utilizing ANOVA, standard deviation, correlation, and the Honesty Significant Differences (HSD) test at a 5% significance level. The study's results were in the open field. The seedlings on the third level of shelves received the highest intensity of sunlight so that the chlorophyll content, seedling height, and number of leaves were relatively higher than those on the second and first level shelves. In greenhouse cultivation, the substitution for LED grows light until 150 Watts between 12 and 14 hours, causing low light intensity, chlorophyll levels, seedling height, and fewer leaves than in open fields.